Intervarietal variation in salt tolerance of lentil (Lens culinaris Medik.) in pot experiments - Hossain, Mohammad Zabed; Hasan, Md Mehedi; Kashem, Md Abul (Bangladesh Journal of Botany, 2018)
Seven lentil (Lens culinaris Medik.) varieties were grown in pots irrigated with NaCl solution of different concentrations (0, 100, 200 and 300 mM) to assess their salinity tolerance potentials. Data revealed that the highest and the lowest salt tolerance were shown by BARI masur-5 (168.50%) and BARI masur-2 (56.32%), respectively. Cluster analysis based on the salt tolerance indices also showed grouping of the varieties into 4 clusters where BARI masur-5 was found highly salt tolerant, BARI masur-6 was moderately salt tolerant and BARI masur-1 and BARI masur-2 were least tolerant. Although shoot height, fresh weight and water content decreased, root length and root to shoot ratio increased significantly with the increase of salt concentrations in the varieties tested.